Flowtube data from the Mendaram peat swamp in Brunei Darussalam - Alexander R Cobb; Charles Franklin Harvey (PANGAEA, 2019)
The flowtube described in this flowtube geometry dataset encloses the piezometers and througfall gauges. The centroid of the throughfall gauges is taken as the location of the flowtube (in the location dataset). The areas and integrated gradients provided in the flowtube geometry dataset were used to calculate the two-dimensional Laplacian of the peat surface elevation, used in Cobb and Harvey (2019).
In supplement to: Cobb, AR; Harvey, CF (2019): Scalar Simulation and Parameterization of Water Table Dynamics in Tropical Peatlands. Water Resources Research, 55(11), 9351-9377, https://doi.org/10.1029/2019WR025411